INOVASI MODEL PEMBIAYAAN MUDHARABAH OLEH INDUSTRI KEUANGAN NON BANK (IKNB) TERHADAP USAHA PENGOLAHAN TERASI - Achmad Kholiq; Nono Hartono; Ah. Fathonih (Jurusan Akuntansi Politeknik Negeri Bandung, 2019)
Shrimp pasta processing business capital sources in Cirebon 62% comes from private funds and only 9% comes from banks. Based on the response the identification of SMEs to the Islamic bank by using ANN showed a medium response. SMEs still assume there is no difference between Islamic banks with conventional due to minimal knowledge of Islamic banks. The MEV value obtained on the use of technology semimodern and production during the rainy season. That is the use of semi-modern technology will be able to increase revenues high when supply of raw materials (rebon) widely available.Innovation mudaraba models by IKNB for processing shrimp is to provide incentives on the number of payments and the differences in the results between the dry season to rainy season on account of helping because Mudhorib revenue decline.